"Friendship" blockaded: The Russia/Belarus conflict is a post-Soviet turning point - Rainer Lindner (Stiftung Wissenschaft und Politik (SWP), 2007)
By raising the gas price for Belarus, buying a major stake in the Belarussian gas pipeline network, imposing export duty on Russian oil deliveries to Belarus, and restricting duty-free import of Belarussian goods to Russia, the Russians have ended an era in relations between the two states. The heart of the 'United State of Russia and Belarus' - the customs union - has been made obsolete at a stroke. Russia's economic policy toward its western neighbor is part and parcel of a new foreign policy that - as the Putin era comes to a close - is focusing increasingly on the national interest. The Lukashenko system, whose economic and political stability were based on the cheap oil supplies from Russia, has been plunged into a serious existential crisis. For the EU and Germany this renewed disruption to energy relations reveals the fragility of the 'strategic partnership' with Russia and the lack of an effective energy dialogue with the transit state of Belarus. (SWP Comments / SWP)
Keywords: 320